Annealing Induced Mechanical Reinforcement of Injection Molded iPP Parts - Pan, Yamin; Liu, Xian Hu; Shi, Suyu; Liu, Chuntai; Dai, Kun; Yin, Rui; Schubert, Dirk W.; Zheng, Guoqiang; Shen, Changyu (Macromolecular Materials and Engineering, 2016)
The mechanical properties and microstructure of injection molded isotactic polypropylene parts with high orientation before and after annealing are analyzed. The mechanical properties of the annealed samples are improved effectively. Through thorough analysis of various structural characterizations, a microstructural model based on the fact that the total length of long period kept constant to analyze the variation of mechanical properties is proposed. It is suggested that the increase of overall crystallinity, the recombination of crystalline phase, and the increase of amorphous phase, respectively, are beneficial for the improvements of the strength, stiffness, and toughness of annealed samples.
Keywords: Injection molding; Mechanical properties; Microstructure; Orientation